Magnitude and determinants of drug therapy problems among type 2 diabetes mellitus patients with hypertension in Ethiopia - Belayneh Kefale; Gobezie T Tegegne; Yitayih Kefale; Mulugeta Molla; Amien Ewunetei; Amsalu Degu (SAGE Open Medicine, 2020)
Introduction: Type 2 diabetes mellitus patients with hypertension are at high risk of drug therapy problems since they are subject to receive multiple drug therapies due to comorbidities. Objectives: To determine the magnitude of drug therapy problems and its determinants among Type 2 diabetes mellitus patients with hypertension. Methods: A cross-sectional study was employed among 423 randomly selected participants based on the inclusion criteria. A structured questionnaire and review of patients’ medical record were employed in the data collection. The classification system used by Cipolle was used to classify and evaluate drug therapy problems. Data were analyzed using Statistical Package for the social sciences version 25.0 software. Multivariate logistic regression analysis was used to identify determinants of drug therapy problems with a statistical significance of p  ⩽ 0.05. Results: A total of 491 drug therapy problems with a mean of 1.86 ± 0.53 drug therapy problems per patient were identified, and 62.4% (264) of them experienced at least one drug therapy problem. Non-compliance (197, 40.1%), needs of additional drug therapy (119, 24.2%), and dosage too low (91, 18.5%) were the most frequently observed drug therapy problems in the study setting. Anti-diabetic medications (88.4%), statins (44.5%), and aspirin (33.5%) were the most commonly involved drugs in drug therapy problems. The determinants of drug therapy problems were very low family income (adjusted odds ratio = 4.64, p   =  0.010), age (45–65 years old) (adjusted odds ratio = 2.55, p  = 0.008), presence of comorbidity (adjusted odds ratio = 9.19, p  < 0.001), and taking ⩾5 medications (adjusted odds ratio = 2.84, p  = 0.001). Conclusion: Approximately three out of five patients had one or more drug therapy problems encountered. In this study, the most common types of drug therapy problems were non-compliance, needs additional drug therapy, and dosage too low. Family monthly income, age, comorbidities, and number of medications were the significant determinants of drug therapy problems. Therefore, patient education regarding medication adherence, routine medication review, and strengthening clinical pharmacy services should be promoted.